2017
DOI: 10.3177/jnsv.63.69
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Total Folate, Folate Species and Polyglutamyl Folate Distribution in Winged Beans (<i>Psophocarus tetragonolobus</i> (L) DC) from Different Cultivars and Growth Stages by Ultra-High Performance Liquid Chromatography Tandem Mass Spectrometry

Abstract: Summary Winged beans are an important natural source of some micronutrients. This paper presents the first complete characterization of folate derivatives including polyglutamyl 5-methyltetrahydrofolate (5-CH3-H4PteGlun), folate species and total folate accumulating in pods and immature seeds of winged beans from 9 cultivars and 7 growth stages. 5-CH3-H4PteGlun and folate species were determined with a UHPLC-MS/MS method. Accurate determination of 5-CH3-H4PteGlun and folate species was optimized and validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Chicken pancreas is only able to remove polyglutamyl tail until diglutamate forms and it is, therefore, combined with some other deconjugases in LC-MS/MS analysis. Rat plasma/serum are the most commonly used, probably due to the commercial availability and very low amounts of endogenous folates [32,33,[35][36][37]. In 1990, Martin et al [38] introduced tri-enzyme treatment which included the use of α-amylase and protease prior the GGH in order to release folates from food matrix and improve their extraction.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…Chicken pancreas is only able to remove polyglutamyl tail until diglutamate forms and it is, therefore, combined with some other deconjugases in LC-MS/MS analysis. Rat plasma/serum are the most commonly used, probably due to the commercial availability and very low amounts of endogenous folates [32,33,[35][36][37]. In 1990, Martin et al [38] introduced tri-enzyme treatment which included the use of α-amylase and protease prior the GGH in order to release folates from food matrix and improve their extraction.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…To take into consideration folate brought by the fermentation reagents, the endogenous folate content in the fermentation reagents was determined as suggested in early reports (10,18). Specifically, 5-g samples of fermentation reagents (pectinase and ACTIFLORE F33 yeast) were suspended in 20 ml of an extraction buffer (100-mM ammonium acetate; 1% ascorbic acid; 0.2% 2mercaptoethanol; pH, 7.89) and homogenized for 2 min using a homogenizer (IKA T18 Basic; IKA, Staufen, Germany) at 4 • C. The homogenates were immediately boiled for 15 min, cooled on ice to room temperature, and reconstituted to 25 ml.…”
Section: Folate Analysis In Fermentation Reagentsmentioning
confidence: 99%
“…Although this method is adequate for determining total folate content, it cannot distinguish diverse folate vitamers ( 7 ). Previously, we developed a UHPLC-MS/MS method for quantification of different folate vitamers in different plants with high sensitivity and accuracy ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Almost the entire research focuses on the respective monoglutamates after enzymatic deconjugation of the polyglutamate vitamers [20,49,63]. Only a few studies focused on the polyglutamate distribution of mammalian tissue [64,65], bacteria [65] and raw vegetables [64,[66][67][68]. Yeast, however, has not been analyzed in terms of polyglutamate vitamers which typically account for the major occurring form in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative materials such as weak anion exchange materials [78], phenyl [74,[79][80][81] or C18 [82][83][84]-modified materials are used less frequently. Few studies also reported the use of hydrophilic-lipophilic-balanced (HLB) materials consisting of N-vinylpyrrolidon-divinylbenzol copolymers offering application for a broad range of analytes [66,85]. We wanted to compare different protocols for their applicability to studies of folate metabolites.…”
Section: Introductionmentioning
confidence: 99%